HOME YARD FOR GARDENING: SOCIALIZATION IN RT 28, KARANGANYAR VILLAGE, PALEMBANG CITY - Haperidah Nunilahwati; Marlina Marlina; Asmawati Asmawati; Yani Purwanti; Rastuti Kalasari; Fitri Yetty Zairani; Burlian Hasani; Joni Philep Rompas; Neni Marlina; Keti Purnamasari (Altifani Journal: International Journal of Community Engagement, 2024)
Urban homestead gardens are generally small, resulting in a lack of green space. Using home gardens as a place for gardening can improve food security and health, especially in urban areas. The counseling aims to socialize the benefits of home gardens for gardening as a source of nutrition or food, and conservation of biodiversity. In collaboration with the Faculty of Agriculture, University of Palembang, Community Service (PKM) activities by the PKM Team were carried out on February 29, 2024, in Karanganyar Village, Palembang City. The method used was counseling including presentation of materials, discussion (questions and answers), and distribution of questionnaires. Data analysis from the questionnaire showed that the highest percentage of participants who knew the benefits of gardening in their home gardens was 73.33%. Those who had home gardens were 66.67%, those who had gardened in their home gardens were 60% and whether they were satisfied with their current home gardens were 53.33%. This extension activity was successful with a 100% good response and the satisfaction level was 53.33% satisfied, 46.67% very satisfied, and 0% dissatisfied. Extension regarding the use of home yards for gardening requires assistance and follow-up from the Extension Team and related parties, especially the local government in the next program stage which includes training or direct practice and evaluation of yard land management for gardening. Support and motivation need to be provided by fellow village residents and the local government.